Unlocking Global Markets for SMEs: The Power of Network Ties and Embeddedness Theory - Alexandra L. Galli-Debicella (Journal of Management Research, 2024)
In today’s global economy, small and medium sized enterprises (SMEs) have greater opportunities to venture into foreign markets—an opportunity that was less feasible a few decades ago. While macro-factors of free-trade and lower transaction costs are the necessary conditions for all firms to expand globally, these are not sufficient for SMEs to expand. SMEs face significant challenges in entering new geographic markets due to their small size and the need for partnerships. Unlike larger firms, SMEs lack “natural market mechanism” to penetrate foreign markets. Instead, small and medium sized enterprises must rely on network ties to opportunistically expand internationally. Drawing from academic literature around embeddedness theory and network ties, this paper explores effective strategies for SMEs aiming to achieve global expansion. Specifically, how small and medium sized enterprises form effective international partnerships, with a focus on the benefits of weak ties over strong ties in providing complementary knowledge, broader access to partners, and avoiding entanglements.